2016
DOI: 10.5152/turkjorthod.2016.160007
|View full text |Cite
|
Sign up to set email alerts
|

Do Different Orthodontic Malocclusions Affect Patients’ Self-Concept and Psychosocial Status?

Abstract: Objective: The aim of this study was to evaluate the self-concept and psychosocial status measured by the levels of social phobia and loneliness in a sample of adolescent patients with different malocclusions and to explain the relationships, if any, between malocclusions. Methods:This study was performed on 90 (41 females and 49 males) orthodontic patients with a mean age of 13.52±1.81 years. The patients were divided into three groups (Class I, Class II, and Class III) according to the different types of mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In addition, Önçağ et al 12 found no significant relationship between the perception of malocclusion and self-esteem in their study. Çokakoğlu et al 31 also found that different malocclusions do not affect a person's self-concept. In our study, no significant relationship was found between the perception of orthodontic malocclusion and self-esteem, because with the aesthetic component of the IOTN, only the dental appearance of individuals can be evaluated.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, Önçağ et al 12 found no significant relationship between the perception of malocclusion and self-esteem in their study. Çokakoğlu et al 31 also found that different malocclusions do not affect a person's self-concept. In our study, no significant relationship was found between the perception of orthodontic malocclusion and self-esteem, because with the aesthetic component of the IOTN, only the dental appearance of individuals can be evaluated.…”
Section: Discussionmentioning
confidence: 98%
“…This theory has been adapted from literature on occupational therapy, which indicated that experiencing deep pressure can be calming to the sensory systems of people with ASD, justifying the use of a restraint board (9,10). On the other hand, our patient had moderate behavior problems with orthodontic treatment; therefore, we did not use a physical restraint as there was no need for it (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…2 A study by Çokakoglu et al for assessment of the self-concept and psychosocial status in adolescent patients with different malocclusions and found that different type of malocclusions don't affect patient's self-concept and psychosocial health. 3 Traumatic injuries to maxillary incisors can occur at any age, but its prevalence is high among children. It can be affected by factors such as age, sex, socioeconomic status and behavioural problems.…”
Section: Introductionmentioning
confidence: 99%